Non-invasive exhaled volatile organic biomarker analysis to detect inflammatory bowel disease (IBD). Issue 2 (February 2016) - Arasaradnam, Ramesh P.; McFarlane, Michael; Daulton, Emma; Skinner, Jim; O'Connell, Nicola; Wurie, Subiatu; Chambers, Samantha; Nwokolo, Chuka; Bardhan, Karna; Savage, Richard; Covington, James
Abstract: Introduction: Early inflammatory bowel disease (IBD) diagnosis remains a clinical challenge. Volatile organic compounds (VOCs) have shown distinct patterns in Crohn's disease (CD) and ulcerative colitis (UC). VOC production, reflecting gut fermentome metabolites, is perturbed in IBD. VOC sampling is non-invasive, with various compounds identified from faecal, breath and urine samples. This study aimed to determine if FAIMS (field asymmetric ion mobility spectroscopy) analysis of exhaled VOCs could distinguish IBD from controls. Methods: Seventy-six subjects were recruited, 54 established IBD (25 CD, 29 UC) and 22 healthy controls. End expiratory breath was captured using a Warwick device and analysed by FAIMS. Data were pre-processed using wavelet transformation, and classification performed in a 10-fold cross-validation. Feature selection was performed using Wilcoxon rank sum test, and sparse logistic regression gave class predictions, to calculate sensitivity and specificity. Results: FAIMS breath VOC analysis showed clear separation of IBD from controls, sensitivity: 0.74 (0.65–0.82), specificity: 0.75 (0.53–0.90), AUROC: 0.82 (0.74–0.89), p -value 6.2 × 10 −7 . IBD subgroup analysis distinguished UC from CD: sensitivity of 0.67 (0.54–0.79), specificity: 0.67 (0.54–0.79), AUROC: 0.70 (0.60–0.80), p -value 9.23 × 10 −4 . Conclusion: This confirms the utility of exhaled VOC analysis to distinguish IBD from healthy controls, and UC from CD. It conforms to other studies using different technology, whilst affirming exhaled VOCs as biomarkers for diagnosing IBD.